“Teks Tertulis sebagai Akses Utama dalam Pembelajaran: Studi tentang Pengalaman Mahasiswa dengan Hambatan Pendengaran di Pendidikan Tinggi Inklusif” - Mayasari Manar; Murni Winarsih (CV. Pusdikra Mitra Jaya, 2026)
Students with hearing impairments must have equitable access to education in order for higher education to be considered truly inclusive. This is particularly crucial in lecture settings where the primary mode of instruction is spoken communication. These days, written content such as presentation slides and subtitle is a typical form of assistance. Examining how well written materials can support students with hearing impairments in inclusive higher education settings is the aim of this study. Students' open-ended responses were analyzed in this study using a descriptive qualitative methodology. The findings demonstrate that written content is a significant source of information, facilitates independent review, and aids in lecture comprehension. However, the intricacy of scholarly language and the errors inherent in automatic transcriptions pose significant challenges. The usage of complicated and difficult-to-understand academic terminology, delays in subtitles, and the unreliability of automatic transcribing present serious difficulties. By demonstrating how crucial language clarity, material structure, and subtitle accuracy are to creating learning designs that are simpler for all students to understand, this study supports inclusive teaching practices. This study demonstrates that written language should not be regarded merely as an optional intervention, but rather as a fundamental component of inclusive, effective, and equitable learning processes. In this regard, it holds significant implications for educators, policymakers, and all stakeholders involved in the development and design of higher education curricula.